2015
DOI: 10.1177/0095399715623315
|View full text |Cite
|
Sign up to set email alerts
|

Performance Audits and Supreme Audit Institutions’ Impact on Public Administration: The Case of the Office of the Auditor General in Norway

Abstract: Performance audit is widespread but contested. The "audit society" proposition holds that audits are rituals producing comfort, whereas the "mandatory audit" proposition in public policy presumes that audits have positive impacts. Common to both propositions is the lack of empirical evidence of audit impact. This article analyzes survey data of the auditees' tendency to make changes as a consequence of Supreme Audit Institutions' performance audits. Civil servants who had experienced performance audits respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 67 publications
(91 reference statements)
0
47
0
3
Order By: Relevance
“…Since Van Loocke and Put () conducted their review, several other empirical impact studies have been published, including Morin (, ), Raudla, Taro, Agu, and Douglas (), Reichborn‐Kjennerud (), Reichborn‐Kjennerud and Johnsen (), and Torres et al. ().…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Van Loocke and Put () conducted their review, several other empirical impact studies have been published, including Morin (, ), Raudla, Taro, Agu, and Douglas (), Reichborn‐Kjennerud (), Reichborn‐Kjennerud and Johnsen (), and Torres et al. ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…(). These studies indicate different levels of impacts, from relatively low impact in countries using no systematic or a French (court model) accountability regime (Morin, ), to modest impact in Canada (Morin, ) and Estonia (Raudla et al., ), and high impact in countries using an Anglo‐American (UK‐Nordic) (Reichborn‐Kjennerud, ; Reichborn‐Kjennerud & Johnsen, ) or Germanic way (Torres et al., ). What seems to determine the positive impacts – that is, that the audits result in actions being taken – is the presence of a legal mandate for the performance audit.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although Parliament must be technically capable to manage SAIs’ information to hold entities to account (Reichborn‐Kjennerud & Johnsen, ), none of the SAIs in this research reported publicly on how they assist Parliamentary bodies to improve their technical capacity in order to carry out their oversight roles. One explanation for this might be because, under the insurance hypothesis for audit (Hay, Simpkins, & Cordery, ), Parliament may wish the auditor to act as a scapegoat for an entity's management's failures and it suits the Public Accounts Committee not to shoulder the blame for such failures; although the omission might simply be because the SAIs were not asked to provide this service.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the agency approach assumes that SAIs could influence the public administration and politicians and the legislature could influence the SAI. Reichborn‐Kjenneurud and Johnsen () analyzed how SAIs’ performance audits influenced public administration in Norway from the rational‐instrumental and cultural‐institutional perspectives. They found that both helped to explain the extent that performance audits influenced the auditees’ changes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%